ACCOUNTING FOR INTANGIBLE ASSETS. - Avery, Harold G. (The Accounting Review, 1942)
The article discusses accounting for intangible assets. Intangible assets are generally grouped into two classes: those subject to amortization and those that are not. Practically all of the intangible items are subject to amortization with the exception of goodwill, trade names and trademarks. At the time of acquisition, the valuation of intangible assets is based on actual cost, either cash or equivalent value. After original cost has been established on the books, the intangible items are valued at cost less amortization, provided the class of intangible property is subject thereto. Where a right or privilege is purchased for cash, no one will object to the listing of that intangible item in the accounts of the company at its purchase price. Also if legal fees, models, drawings, development expenses and defense costs under a litigation proceeding are expended in order to acquire, develop, or protect an asset of this nature, the total expenditure can be capitalized as the cost of the asset. When intangible assets are not subject to amortization, yet they have been paid for and the values duly recorded, the question arises as to what shall be done with these amounts as the years go by.